The Birth Prevalence of Spinal Muscular Atrophy: A Population Specific Approach in Estonia - Sarv, Siiri; Kahre, Tiina; Vaidla, Eve; Pajusalu, Sander; Muru, Kai; Põder, Haide; Gross-Paju, Katrin; Ütt, Sandra; Žordania, Riina; Talvik, Inga; Õiglane-Shlik, Eve; Muhu, Kristina; et al. (Frontiers in Genetics, 2021)
Background. Rare diseases are an important population health issue and many promising therapies have been developed in recent years. In light of novel genetic treatments expected to significantly improve spinal muscular atrophy (SMA) patients’ quality of life and the urgent need for SMA newborn screening (NBS), new epidemiological data were needed to implement SMA NBS in Estonia. Objective. We aimed to describe the birth prevalence of SMA in the years 1996–2020 and to compare the results with previously published data. Methods. We retrospectively analyzed clinical and laboratory data of SMA patients referred to the Department of Clinical Genetics of Tartu University Hospital and its branch in Tallinn. Results. Fifty-seven patients were molecularly diagnosed with SMA. SMA birth prevalence was 1 per 8,286 (95% CI 1 per 6,130–11,494) in Estonia. Patients were classified as SMA type 0 (1.8%), SMA I (43.9%), SMA II (22.8%), SMA III (29.8%), and SMA IV (1.8%). Two patients were compound heterozygotes with an SMN1 deletion in trans with a novel single nucleotide variant NM_000344.3:c.410dup, p.(Asn137Lysfs*11). SMN2 copy number was assessed in 51 patients. Conclusion. In Estonia, the birth prevalence of SMA is similar to the median birth prevalence in Europe. This study gathered valuable information on the current epidemiology of SMA, which can guide the implementation of spinal muscular atrophy to the newborn screening program in Estonia.